APPLICATION OF CFD SOFTWARE FOR AERODYNAMICS ANALYSIS OF TOYOTA INNOVA AND TOYOTA YARIS - Wirawan, Mohammad
Toyota Innova and Toyota Yaris are types of car that are often found in Indonesia. Spoiler is often installed on the back of Toyota Yaris and Toyota Innova. This undergraduate assignment contain an analysis of the effect of spoilers on cars that are often found in Indonesia, namely the Toyota Innova and Toyota Yaris using computational fluid dynamics analysis. The modeling of the cars was carried out using the SolidWorks 2021 software based on the blueprints of the cars. Computational fluid dynamics analysis was performed using ANSYS software. The parameters obtained from the simulation are drag coefficient, lift coefficient, pressure contour, and fluid velocity vector that interacts with the car body. It is found that the drag coefficient of the Innova without and with spoiler is 0.474 and 0.477 respectively, while the Yaris drag coefficient without and with spoiler is 0.452 and 0.460 respectively. Innova lift coefficient without and with spoiler is found to be 0.0128 and -0.133 respectively, while Yaris lift coefficient without and with spoiler is 0.048 and -0.0152 respectively. It can be seen that spoilers on hatchback cars such as Toyota and Toyota Yaris increases drag coefficient and decreases lift coefficient.